Pencegahan Perundungan/Bullying di Institusi Pendidikan: Pendekatan Hak Asasi Manusia (HAM) - Siregar, Ehdatul Puadi; F, Firman; Sukma, Dina (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to study the phenomenon of bullying in schools. Departing from the condition of "bullying emergency" declared by the mass media, this study uses a qualitative approach to identify the factors that cause bullying and the prevention efforts that have been taken.  Although the government has issued regulations such as the Child Protection Law and Permendikbud Number 82 of 2015, its implementation is still limited and spatial.  Data were collected through literature studies and empirical data obtained from the experiences of junior high school (SMP) and high school (SMA) students in Semarang City.  The results of the research are expected to contribute to formulating more effective and comprehensive bullying prevention strategies in the school environment, as well as increasing awareness of the importance of creating a safe and inclusive learning environment.